A MISTAKE IN THE KNOWLEDGE OF THE LAW IN THE CONTEXT OF CRIMINAL OFFENSES AGAINST THE ENVIRONMENT - Elek, Balázs (Glasnik Advokatske komore Vojvodine, 2025)
One of the consequences of deepening criminal law cooperation with European integration may be a further increase in the body of law that those involved in a particular area of law need to know. It is no longer only a question of navigating the maze of internal law, but also of navigating the even more complex system of European legal development, the world of directives, framework decisions, Commission decisions and regulations. There are also a number of criminal law provisions which are directly fleshed out by EU rules. In this legal environment, even lawyers wishing to specialise in a more restricted field sometimes find it difficult to navigate, which raises the question of whether a plea of 'legal error' (the mistake in the knowledge of the law) can be accepted in the absence of knowledge of the law[AT1] .  [AT1]We need longer introduction.
Keywords: mistake in the knowledge of the law; environmental crime; consciousness of illegality